The importance of forests and natural habitats - ecotheological and human-ecological aspects - Ferenc Mics (Opuscula Theologica et Scientifica)
Forests and natural ecosystems are essential for sustaining life on our planet, playing a critical role in maintaining biodiversity, regulating climate patterns and facilitating the hydrological cycle. However, these critical ecosystems face a range of threats, from deforestation to climate change, requiring concerted efforts by global, national and local stakeholders to ensure their conservation. This paper explores the emergence, prominent figures, key perspectives and recent influences of ecotheology. The interconnectedness of ecological, economic and cultural dimensions highlights the urgent need for effective conservation strategies and mitigation policies at all levels, from grassroots initiatives to global agreements, to protect and sustainably manage these invaluable natural resources. The historical, current and future functions of forests in these contexts illustrate the importance of collaborative efforts combining ecological responsibility with theological insights and the evolving field of human ecology.